Can Medical Students Lead Effective Quality Improvement Initiatives? A Systematic Review. (March 2019) - Sayma, Meelad; Saleh, Dina; Saleh, Keenan; Gaukroger, Andrew; Howard, Theodore; Hesford, Christian; Williams, Hywel Rhys; Ejaimike, Lady-Namera; Zolfaghari, Yasmin; Ong, Ashley
Quality improvement project (QUIP) concepts are becoming embedded into medical school curricula, with many students now expected to conduct a QUIP as part of their progression. This study aimed to assess whether student-led QUIPs can be effective and sustainable. A systematic literature search was conducted using 5 databases: MEDLINE, Embase, Ovid, CINAHL, and PsycINFO. The authors searched for articles published between January 28, 1978, and January 28, 2018. In all, 3965 articles were identified through database searching, and an additional 9 articles through hand searches. After screening and full-text analysis, 12 articles were included. Greater than 50% of QUIPs described a statistically significant improvement in the primary outcome. However, effective student-led QUIPs were not necessarily sustainable, with a mean final audit at 4.4 months. Medical students have the potential to produce effective QUIPs. There now needs to be a structured approach to give medical students the freedom to test and validate more unique interventions.